Multielectron Redox Catalysis with Efficient Tyrosinase Activity Based on a Visible‐Light Controlled Artificial Photoenzyme. Issue 20 (20th April 2020) - Reichl, Eva; Ertl, Martin; Knör, Günther
Abstract : A stepwise non‐enzymatic conversion of the natural amino acid L ‐tyrosine into physiologically relevant intermediates L ‐DOPA, dopaquinone and dopachrome has been demonstrated in aqueous solution under ambient conditions. The photocatalytic redox process applied involves controlled activation of molecular oxygen forming water and hydrogen peroxide as further reaction products. Substrate conversion can be switched on and off conveniently by regulating the degree of visible‐light or sunlight exposure of an immobilized multielectron transfer sensitizer, which is very easy to apply and can be separated again from the supernatant reaction medium. Quantitative analysis of the six‐electron redox conversion of L ‐tyrosine catalyzed by the artificial oxidoreductase enzyme system reveals a remarkable degree of abiotic phenolase activity which nearly approaches the benchmark value of the native metalloenzyme tyrosinase under substrate saturation conditions. Abstract : Abiotic Oxidase Reaction Cascades: An immobilized antimony‐oxo porphyrin derivative is applied as visible‐light driven photocatalyst promoting the aromatic hydroxylation of L ‐tyrosine, followed by a stepwise four‐electron oxidation to generate the natural product dopachrome. The biomimetic diphenolase activity of the artificial enzyme is comparable to native tyrosinase.